Hope is an imperative the essential David Orr - Orr, David W. 1944- (Island Press, 2011)
For more than three decades, David Orr has been one of the leading voices of the environmental movement, championing the cause of ecological literacy in higher education, helping to establish and shape the field of ecological design, and working tirelessly to raise awareness of the threats to future generations posed by humanitys current unsustainable trajectory.   Hope Is an Imperative brings together in a single volume Professor Orrs most important works. These include classics such as What Is Education For one of the most widely reprinted essays in the environmental literature, The Campus and the Biosphere, which helped launch the green campus movement,and Loving Children: A Design Problem, which renowned theologian and philosopher Thomas Berry called the most remarkable essay I've read in my whole life. The book features thirty-three essays, along with an introductory section that considers the evolution of environmentalism, section introductions that place the essays into a larger context, and a foreword by physicist and author Fritjof Capra.   Hope Is an Imperative is a comprehensive collection of works by one of the most important thinkers and writers of our time. It offers a complete introduction to the writings of David Orr for readers new to the field, and represents a welcome compendium of key essays for longtime fans. The book is a must-have volume for every environmentalists bookshelf.